2007
DOI: 10.1016/j.ejheart.2006.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic significance of atrial fibrillation in outpatients with heart failure due to left ventricular systolic dysfunction

Abstract: Introduction: Atrial fibrillation (AF) is common in patients with heart failure (HF) due to left ventricular systolic dysfunction (LVSD), with conflicting prognostic data. The aim of our study was to assess the prevalence and incidence of AF in patients with HF and to determine the prognostic impact of baseline AF and the development of new onset AF. Methods and results:We included 1019 outpatients with HF due to LVSD; follow-up time ranged from 3 to 64 months. At baseline 26.4% of patients had AF. Of the 284 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 36 publications
(68 reference statements)
1
44
1
5
Order By: Relevance
“…1,2,7-9,19, 20 In the present study, we analyzed the subset of HF patients most affected by AF, which included a relatively high percentage of patients with low BMI compared with Western studies. 21- 23 The main findings were as follows: (1) the risk of the composite primary endpoint (all-cause death and re-hospitalization for ADHF) was higher in patients with AF than in those without AF; (2) the incidence rate of the primary endpoint was higher in patients with AF from the HFpEF group, but not the HFrEF group; (3) the incidence rate of the primary endpoint was higher in patients with AF from the HFpEF group who had low-medium BMI; and (4) AF was an independent predictor of the endpoint only in the HFpEF BMI <25 group.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,7-9,19, 20 In the present study, we analyzed the subset of HF patients most affected by AF, which included a relatively high percentage of patients with low BMI compared with Western studies. 21- 23 The main findings were as follows: (1) the risk of the composite primary endpoint (all-cause death and re-hospitalization for ADHF) was higher in patients with AF than in those without AF; (2) the incidence rate of the primary endpoint was higher in patients with AF from the HFpEF group, but not the HFrEF group; (3) the incidence rate of the primary endpoint was higher in patients with AF from the HFpEF group who had low-medium BMI; and (4) AF was an independent predictor of the endpoint only in the HFpEF BMI <25 group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AF seemed to be a stronger predictor of negative outcome in the subset of patients with mild to moderate heart failure compared with patients with severe heart failure, in whom the contribution of AF to further impairment in survival was limited. Similarly, Corell et al 52 found that the presence of AF in outpatients with heart failure also was associated with increased morbidity and mortality and that AF was a stronger predictor of adverse outcome in patients with better cardiac function (LVEF Ͼ35%). In the Trandolapril Cardiac Evaluation (TRACE) study, Pedersen et al 53 found that long-term mortality was increased in all subgroups of patients with AF except those with the most advanced disease (LVEF Ͻ25%).…”
Section: The Association Between Af and Heart Failurementioning
confidence: 99%
“…17,18 Interestingly, the mere occurrence of AF in this patient population carries an increased risk of morbidity and mortality. 2,19,20 QRS duration (QRSd) is also associated with an increased mortality and morbidity in patients with CHF. 21 -23 A wide QRS in this setting is associated with more myocardial disease No conflict of interest to report.…”
Section: Introductionmentioning
confidence: 99%